2021
DOI: 10.1037/edu0000620
|View full text |Cite
|
Sign up to set email alerts
|

The role of STEM professors’ mindset beliefs on students’ anticipated psychological experiences and course interest.

Abstract: Two decades of research consistently demonstrates that students’ beliefs about the malleability of intelligence (also known as “mindsets”) influence their motivation and academic outcomes. The current work provides a novel extension to this literature by examining how STEM professors’ mindset beliefs can influence students’—and particularly female students’— anticipated psychological experiences and interest in those professors’ courses. In 3 experiments, college students evaluated STEM courses taught by profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 84 publications
3
54
0
Order By: Relevance
“…A recent study shows the power of the perceived beliefs of STEM faculty members ( LaCosse et al, 2020 ). The researchers had students evaluate STEM courses that were taught by professors who, via random assignment, either expressed fixed or growth mindset beliefs about intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows the power of the perceived beliefs of STEM faculty members ( LaCosse et al, 2020 ). The researchers had students evaluate STEM courses that were taught by professors who, via random assignment, either expressed fixed or growth mindset beliefs about intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent experiment, when a teacher expressed a colorblind (versus multicultural) ideology in class, students of color perceived that the teacher was more racially biased and performed worse on a quiz at the end of the class, whereas White students were not affected [39]. Additionally, although teachers' expression of fixed or non-universal ability beliefs may harm all students [92], members of marginalized social groups may be disproportionately affected due to prevalent negative stereotypes about their ability [28,32,93,94]. For example, a recent series of studies found that the negative effects of a teacher expressing non-universal ability beliefs on students' anticipated performance, belonging, and interest in a class were 36-64% larger among women than men [94].…”
Section: Disparate Impactmentioning
confidence: 99%
“…Additionally, although teachers' expression of fixed or non-universal ability beliefs may harm all students [92], members of marginalized social groups may be disproportionately affected due to prevalent negative stereotypes about their ability [28,32,93,94]. For example, a recent series of studies found that the negative effects of a teacher expressing non-universal ability beliefs on students' anticipated performance, belonging, and interest in a class were 36-64% larger among women than men [94].…”
Section: Disparate Impactmentioning
confidence: 99%
“…It has been observed that high levels in the sense of belonging in university students contributes to increasing their levels of participation, being able to seek help in the face of difficulties, feeling less alone, anxious or depressed, increasing the use of self-regulation strategies and raises levels of academic self-confidence and motivation [64,66,77]. In addition, various investigations have observed that the sense of belonging turns out to be a direct predictor of study engagement, dropout, and permanence in studies [40,41,45,65,66,73,[77][78][79][80].…”
Section: Sence Of Belongingmentioning
confidence: 99%